A Landscape in Transitions: Guletta, a Multiperiod Settlement along the Mazaro River in Western Sicily. (3rd July 2020) - Sevara, Christopher; Salisbury, Roderick B.; Doneus, Michael; Draganits, Erich; Totschnig, Ralf; Frazzetta, Cipriano; Tusa, Sebastiano
ABSTRACT: The Prospecting Boundaries project explores the Mazaro river corridor from a landscape archaeological perspective, using integrated prospection techniques to recover traces of past human activity and environmental contexts. One key research area is Guletta, a zone of dense multiperiod activity situated on the rocky plain above the river. In this paper, we detail results from recent work at Guletta, which has revealed numerous previously undocumented archaeological settlement features that appear to have been built in successive phases. Artifact analysis from corresponding surface survey indicates a mixture of locally produced and imported materials dating from the Middle Bronze to Archaic periods. Using these new results together with existing archaeological and environmental information, we present an initial interpretation of the occupation sequence of the settlement and explore the concept of Guletta as a connecting point between emerging indigenous, colonial, coastal, and interior interdependencies and interests in later pre- and protohistory.